Sakarin Dalam Jeruk Buah Di Pasaran Semasa Malaysia Dan Hubungannya Dengan Konsep Halalan Thoyyiban[Saccharin in Fruit-Pickle in Malaysian Market and Its Relationship with the Concept of Halalan Thoyyiban] - Abdullah, N. S.; Rosman, A. S.; Yaakob, H. (Universiti Sains Islam Malaysia, 2024)
Muslims are required to select halal and good (thoyyiban) food, which comprises the safety aspect. Halal and safety-related issues of food are often being focussed by Muslim people in this country. One of the discussed issues is the safety level of saccharin consumption as an artificial sweetener. This study analysed saccharin from scientific perspectives and its relationships with human health. Then, this study connected the presence of saccharin in fruit-pickle samples with the concept of halalan thoyyiban. In the first phase, this study used qualitative methodologies which includes historical, content analysis, and observation method. As for the second phase, this study used a quantitative methodology based on experiments in the laboratory on six fruit-pickle samples. Findings show that saccharin is produced synthetically and does not contain calories and any nutrients. Saccharin is safe if taken according to the safe limit set by WHO that is 5mg/kg (of body weight) per day. Excessive consumption either contributes or stimulates cancer (tumour promoter). Meanwhile, the quantitative study found that five from six analysed samples of fruit pickles contain saccharin. The safety level measurement towards human between the weight of 20kg up to 50kg that consumes 100g of pickles per day is however still below the safe limit set by WHO. This study concludes that saccharin is halal but cannot be categorised under thoyyiban as it does not contain any nutrient and calory, can give negative effects to health if taken over the suggested amount.